Broken rotor bar detection in LS-PMSM based on startup current analysis using wavelet entropy features - Mehrjou, Mohammad Rezazadeh; Mariun, Norman; Misron, Norhisam; Mohd Radzi, Mohd Amran; Musa, Suleiman (MDPI, 2017)
High-efficiency motors are being gradually introduced in many industrial applications because of their positive impacts on the environment by reducing energy consumption and CO2emission. In this respect, line start permanent magnet synchronous motors (LS-PMSMs) have been introduced recently.Due to their unique configuration, LS-PMSMs allow the obtaining of super premium efficiency levels,accompanied with a high torque and power factor. However, since the use of LS-PMSMs in the industry is in its infancy, no efficient scheme has yet been reported for broken rotor bar (BRB) fault detection in this type of motor. Accordingly, the main aim of this research is to investigate the fault-related feature for BRB faults on LS-PMSMs. In this regard, a simulation model and experimental setup for the investigation of BRB in LS-PMSM are implemented. The detection strategy for BRB in LS-PMSM proposed here is based on the monitoring of the start-up current signal and discrete wavelet transform. The entropy features are used as fault-related features for BRB faults. Finally, the ability of these features is validated for the detection of BRB in LS-PMSM through statistical analysis. In this research, the importance of the starting load is also considered for BRB detection in LS-PMSMs.